Faktor yang Berhubungan dengan Pola Pemberian MP-ASI pada Balita di Wilayah Kerja Puskesmas Oele, Kabupaten Rote Ndao - Rio Brian Mboeik; Honey I. Ndoen; Daniela L. A. Boeky (Universitas Nusa Cendana, 2022)
To achieve optimal growth in toddlers aged 0 to 24 months, the best food is breast milk (ASI), which is a source of balanced nutrition according to the composition and needs of the toddler. Breastmilk is given until toddlers are 6 months old and after 6 months, milk production begins to decline so that toddlers are introduced to complementary foods with breast milk, but breast milk is still given until toddlers are 24 months old. This study aims to determine the factors related to the pattern of complementary feeding to toddlers in the work area of ​​Oele Health Center, Rote Ndao Regency with a cross-sectional study approach. The independent variables of this study were mother's education, mother's knowledge, maternal occupation, family income, and types of complementary foods, while the dependent variable was the pattern of complementary feeding for toddlers aged 6-24 months. The sampling technique in this study was total sampling where the sample was taken was 58 people from the total population of all mothers who had toddlers aged 6-24 months who were analyzed using the chi-square test. The results of the analysis showed that there was a relationship between knowledge and the pattern of complementary feeding (p=0.011) and there was a relationship between types of complementary foods and patterns of complementary feeding and there was no relationship between maternal education (p=0.359) and maternal occupation (p=0.635) and the level of family income (p = 0.201) with the pattern of complementary feeding.